Expressive Writing: A Narrative Counseling Strategy to Improve Boarding School Students' Assertiveness - Fatimah, Vonny; Hidayah, Nur; Hotifah, Yuliati (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2025)
Assertive behaviour is the ability to express thoughts, feelings, and desires without hurting other people's feelings, while still respecting the rights of others and oneself. The purpose of this study was to measure the effectiveness of narrative counselling expressive writing containing systematic revelations to improve the assertive behaviour of boarding school students. This study was an experimental study using a one-group pretest-posttest design. The research subjects were eighth-grade students at a boarding school. The normality test results showed that the significance value for the pre-test was 0.700 > 0.05 and for the post-test was 0.075 > 0.05, indicating that the data were normally distributed. The paired sample test results showed that the sig (2-tailed) value was 0.034 < 0.05, so Ha was accepted and Ho was rejected. The results of the Cohen's d analysis showed a value of 1.27 > 0.8, indicating that the narrative counselling intervention had a significant effect on the students, thereby improving their assertive behaviour.